Colon Cancer: An Unusual Presentation with a Paraneoplastic Syndrome - Reham Almasoud (Karger Publishers, 2021)
Dermatomyositis (DM) is a rheumatological disorder characterized by proximal myositis and distinctive dermatological manifestations. It can be an isolated clinical syndrome or, in rarer cases, can be the initial presentation for an underlying malignancy as a part of a paraneoplastic syndrome. In this case report, we describe a case of a 51-year-old lady who presented with proximal myopathy, typical DM skin rash, dysphagia, and markedly elevated creatine kinase. She was diagnosed with a seronegative DM and her malignancy screening revealed a mass in the ascending colon. During her hospital course, she also developed microangiopathic hemolytic anemia, another paraneoplastic disorder typically associated with late stages of malignancy, manifested as hemolytic anemia, thrombocytopenia, and low fibrinogen. The patient received intravenous corticosteroids and underwent tumor resection with following resolution of her both rheumatological and hematological manifestation. Unfortunately, due to her general poor health, she developed sepsis and died in the hospital.